Post covid-19 complications associated with labor productivity of workers in a regional hospital, Junín - Carrillo Cayllahua , Mirian (2023)
Objective: To determine the association between labor productivity and post COVID-19 complications in workers of the Hospital Docente Materno Infantil El Carmen 2022. Material and Methods: Basic study, correlational level; it used the analysis-synthesis method, with a non-experimental design, had a sample obtained through a formula for finite populations, obtaining 95 health professionals who presented post-COVID-19 complications. Results: 74.74% (71) professionals with post COVID-19 complications have adequate labor productivity; 25.26% (24) professionals with post COVID-19 complications have inadequate labor productivity; 88.42% (84) professionals with post COVID-19 complications have labor productivity in their adequate efficiency dimension; 11. 58% (11) professionals with post COVID-19 complications have labor productivity in their inadequate efficacy dimension; 69.47% (66) professionals with post COVID-19 complications have labor productivity in their adequate efficiency dimension; 30.53% (29) professionals with post COVID-19 complications have labor productivity in their inadequate efficiency dimension. Conclusions: There is correlation between labor productivity and post COVID-19 complications in workers of the Hospital Docente Materno Infantil El Carmen 2022, with Chi-square value 6.044 and pvalue = 0.042 of bilateral significance at 95% probability.